Importância e urgência de uma revisão na abordagem geracional na atualidade: uma proposta - Calliari, Marcos Procópio (2018)
This paper intends to carry out an analysis of the generational approach in the present time and to offer a proposal to reinforce its importance as an analytical tool. For that, its structure comprises a theoretical conceptual discussion and analysis of examples of recent studies in the country, identifying gaps and opportunities, and a recommendation of methodological innovations that could increase its relevance and usage to its full potential. It takes a historical perspective on the subject starting from the analysis of Julian Marias (1949) to address some of the main authors who have deepened the concepts, such as Mentré (1920), Ortega y Gasset (1966), and in particular Mannheim (1952), to more recent authors such as Abrams (1982) and Strauss and Howe (1991). It notes that the current application of the generation approach does not respect the conceptual robustness, causing an underutilization of the approach and its social potential. The paper then presents three distinct examples of recent Brazilian studies with generational ambitions, and discusses the advances and limitations introduced by them. Considering the context identified, it then presents a proposal for methodological innovations, based on the precepts of the École des Annales, which can, by rescuing the analytical depth of the conceptual framework, serve as a stepping stone for future studies and research. While reviewing a tool with high public interest from various perspectives and presenting new possibilities of approach, it seeks to reinvigorate the field of study and its multiple uses.